2017
DOI: 10.1111/bjd.15098
|View full text |Cite
|
Sign up to set email alerts
|

Increased protoporphyrin IX accumulation does not improve the effect of photodynamic therapy for actinic keratosis: a randomized controlled trial

Abstract: Increased PpIX accumulation does not improve the effect of MAL-PDT for AKs on the hands, but leads to worse adverse events. Different strategies are needed to improve PDT on the extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…Curettage has been shown to enhance the subsequent rate of protoporphyrin IX (PpIX) formation . However, the difference between PpIX level in AKs after curettage and no curettage disappears over time .…”
Section: Introductionmentioning
confidence: 84%
“…Curettage has been shown to enhance the subsequent rate of protoporphyrin IX (PpIX) formation . However, the difference between PpIX level in AKs after curettage and no curettage disappears over time .…”
Section: Introductionmentioning
confidence: 84%
“…A mathematic model has demonstrated that daylight produced more local damage (more single oxygen radicals) that the conventional illumination with Aktilite ® even in cloudy days, but this accumulation has not demonstrated more efficacy in in vitro models or clinical trials, suggesting that the determinant factor for cytotoxicity is the total doses applied and not the irradiance or the PpIX accumulation . Moreover, a recent in vitro study has founded that half doses of red light, applied in half time, without changing irradiance are more effective in the induction of cell death of squamous cell carcinoma cells . In this way, a recent study based in a mathematical model compared 10 different protocols of illumination, including conventional red light PDT, daylight PDT and blue light.…”
Section: Discussionmentioning
confidence: 99%
“…They are either applied to remove hyperkeratotic AK in order to improve the permeation capability of topical drugs or to remove single lesions that were not cleared by previous topical therapies. However, high‐quality evidence is lacking as no RCTs and only few case series have been published on shave and complete excision for AK …”
Section: Combination Of Lesion‐ and Field‐directed Regimensmentioning
confidence: 99%